The internationalisation of business angel investment activity: a review and research agenda. Issue 1 (2nd January 2017) - Harrison, Richard T.
Abstract: Prompted by the recent publication of two practitioner-led and -oriented books profiling the global expansion of the business angel investment phenomenon, this paper reviews the evidence for the internationalisation of this increasingly important source of entrepreneurial finance. As business angel activity grows in prominence in emerging markets in particular, challenges are identified in terms of the definition of the phenomenon, the importance of institutional voids in shaping the development of this activity and the role of cultural constraints in legitimising it. The paper identifies a tension between universalist and contextualist accounts of the emergence of this market which has implications for both future research and policy formation.